Psychological and emotional effects in families with one member schizophrenic - Santos-Morocho, José (2020)
The family as a system teaches through communication the relationship patterns that the members put into practice in other contexts. The objective of this research was to characterize communication in nuclear families with adolescent children. Focusing communication as a binding entity within the family system. This study was qualitative of an exploratory type. Thirty nuclear families participated, they had an intentional sample of 10 families with adolescent children between 13 and 17 years old. Data were collected through circular interviews, a focus group topic guide and the application of a questionnaire designed for this purpose. Data was processed by triangulation. The specific results that families handle alternative and specific communication styles of indirect masked typology, being clear and direct is not enough for communication to be functional, if communication exchange is devoid of affect, silencing strategies are part of the communication circuit and not understanding family interaction is possible if it is isolated from the communicational category analysis.